Theoretical aspects of modern economic diplomacy / Tеоретические аспекты современной экономической дипломатии - KROTENKO Yuri (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The prerequisites for the formation of innovative approaches to the development of the modern concept of economic diplomacy are formulated. The international experience of activating national projects in the field of economic diplomacy is described. Proposals are being formulated for the development of public-private partnership in the field of economic diplomacy.